Mutual boosting of the saturation scales in colliding nuclei - Kopeliovich, Boris Z.; Pirner, Hans J.; Potashnikova, I. K.; Schmidt, Iván (Physics letters, 2011)
Saturation of small-x gluons in a nucleus, which has the form of transverse momentum broadening of projectile gluons in pA collisions in the nuclear rest frame, leads to a modification of the parton distribution functions in the beam compared with pp collisions. The DGLAP driven gluon distribution turns out to be suppressed at large x, but significantly enhanced at x≪1. This is a high twist effect. In the case of nucleus-nucleus collisions all participating nucleons on both sides get enriched in gluon density at small x, which leads to a further boosting of the saturation scale. We derive reciprocity equations for the saturation scales corresponding to a collision of two nuclei. The solution of these equations for central collisions of two heavy nuclei demonstrate a significant, up to several times, enhancement of QsA2, in AA compared with pA collisions.